Grammarly As a Digital Learning Tool: Supporting Self-Directed Learning in Academic Writing at Universitas Muhammadiyah Kalimantan Timur - Musyarofah, Riskiyanti; Ramadhan Hamid, Ade Ismail; Halim, Abdul (Borneo Educational Journal (Borju), 2025)
Academic writing is a fundamental skill in higher education, especially for students learning English as a Foreign Language (EFL), who often face challenges in organizing ideas and applying accurate grammar. The integration of artificial intelligence (AI) tools like Grammarly has opened new opportunities for students to improve writing performance independently. This study investigates students' perceptions of Grammarly and examines its role in supporting Self-Directed Learning (SDL), which includes self-management, motivation, and self-monitoring. Employing a quantitative descriptive method, data were collected through a structured questionnaire involving 50 second-semester students enrolled in the Academic Writing course at Universitas Muhammadiyah Kalimantan Timur. The results revealed high average scores in both Grammarly usage (need and practicality) and all three dimensions of SDL. Furthermore, a strong positive correlation (r = 0.869, p < 0.000) was found between Grammarly use and SDL levels. This indicates that students who positively perceive Grammarly are more likely to develop SDL behaviors in academic writing. The study concludes that Grammarly serves not only as a technical writing aid but also as a reflective tool that supports learner autonomy. The originality of this research lies in its focus on linking Grammarly use with SDL in the specific context of Indonesian EFL students an area that remains underexplored in previous studies. This provides valuable insights into how digital writing tools can foster independent learning in academic contexts.